Strategy and structure chapters in the history of the American industrial enterprise - Chandler, Alfred (Massachusetts The Mit Press, 1990)
This book shows how the seventy largest corporations in America have dealt with a single economic problem: the effective administration of an expanding business. The author summarizes the history of the expansion of the nation's largest industries during the past hundred years and then examines in depth the modern decentralized corporate structure as it was developed independently by four companies -- du Pont, General Motors, Standard Oil (New Jersey), and Sears, Roebuck. This 1990 reprint includes a new introduction by the author.
Includes index
Keywords: Industrial management